The Relationship between Internal Locus of Control and Academic Self-Regulation in Class 11 Vocational High School Students in Sidoarjo: Hubungan Antara Internal Locus of Control Dengan Regulasi Diri Akademik pada Siswa Kelas 11 Sekolah Menengah Kejuruan di Sidoarjo - Syahputra, Indra Agi; Affandi, Ghozali Rusyid (Psikologia : Jurnal Psikologi, 2021)
This research is motivated by the phenomenon of students regarding the problem of managing academic self-regulation in learning activities at school. This study aims to determine the relationship between Internal Locus of Control and Academic Self Regulation in class XI students of SMK "X" in Sidoarjo. The research was carried out at SMK "X" Sidoarjo with a sample size of 172 students. The sampling technique used Simple Random Sampling, and data collection used two psychological scales with Likert scale modeling, namely the Internal Locus of Control scale with the Academic Self-Regulation scale. This research data analysis using Pearson Product Moment correlation technique. The results of the data analysis of this study indicate that there is a significant positive relationship between Internal Locus of Control and Academic Self-Regulation in Vocational School "X" Students in Sidoarjo, with a correlation coefficient of 0.501 and a significance level of 0.000 <0.05. The coefficient of determination test also shows a result of 0.251 (R Square) which explains that in this study the Internal Locus of Control variable gives an effective effect of 25.1% on Academic Self-Regulation. The results of testing the hypothesis indicate that the hypothesis can be accepted.